Our Lady of Lourdes, Roman Catholic church in Lourdes - Clarke, Kimberly S. (1994)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Field Trip to Black Duck Brook, Port au Port Peninsula, Newfoundland ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Field Trip to Black Duck Brook, Port au Port Peninsula, Newfoundland".